Treatment of avian malaria in captive African penguins (Spheniscus demersus) by the combination of atovaquone and proguanil hydrochloride - Rossella Samarelli; Nicola Pugliese; Medhat Saleh; Michela Prioletti; Rossana Cordon; Paolo Cavicchio; Dalila Salierno; Giuseppe Crescenzo; Elena Circella; Antonio Camarda (International Journal of Veterinary Science and Medicine)
Avian malaria, a vector-borne disease caused by Plasmodium spp., poses significant threats to various bird populations, particularly captive penguins like the endangered African penguin (Spheniscus demersus). Penguins, originating from regions with low malaria prevalence, are highly susceptible when housed in malaria-permissive areas. This study evaluates the efficacy of an atovaquone/proguanil hydrochloride treatment protocol to manage avian malaria in a captive African penguin colony in an Italian zoo. The study involved 30 penguins monitored over 3 years. Thirteen penguins tested positive for Plasmodium spp., with 11 undergoing treatment. The treatment protocol consisted of atovaquone/proguanil hydrochloride (10/4 mg/kg) administered orally for 3 days, repeated after a week. Post-treatment monitoring at 7, 30, and 60 days, and follow-ups up to 2 years, showed that all but one penguin cleared the infection. The treatment was well tolerated, with no adverse effects observed. The findings suggest that this protocol is effective as a treatment of avian malaria and could be a valuable tool in avian malaria management, particularly for endangered species in captivity. However, the persistence of Plasmodium relictum in one case highlights the need for careful post-treatment monitoring to prevent recurrence or reinfection. The study underscores the importance of developing tailored antimalarial protocols for captive birds to enhance conservation efforts and mitigate the risks posed by avian malaria.